Caloxanthone C: a pyranoxanthone from the stem bark of Calophyllum soulattri. - Ee, Gwendoline Cheng Lian; Siau, Hui Mah; Huey, Chong Kwong; Soek, Sin Teh; Mohamed Tahir, Mohamed Ibrahim; Silong, Sidik (International Union of Crystallography, 2011)
The title compound [systematic name: 5,10-dihydroxy-2,2-dimethyl-12-(2-methylbut-3-en-2-yl)pyrano[3,2-b]xanthen-6(2H)-one], C23H22O5, isolated from the stem bark of Calophyllum soulattri, consists of four six-membered rings and a 2-methylbut-3-en-2-yl side chain. The tricyclic xanthone ring system is almost planar [maximum deviation = 0.093 (2) Å], whereas the pyranoid ring is in a distorted boat conformation. The 2-methylbut-3-en-2-yl side chain is in a synperiplanar conformation. There are two intramolecular O—H(...)O hydrogen bonds. In the crystal, molecules are linked by C—H(...)O interactions, forming a zigzag chain propagating in [010].